Observation of sizeable ω contribution to χc1(3872) → π+ π− J=ψ decays - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review, 2023)
Resonant structures in the dipion mass spectrum from χc1(3872)→π+π−J/ψ decays, produced via B+→K+χc1(3872) decays, are analyzed using proton-proton collision data collected by the LHCb experiment, corresponding to an integrated luminosity of 9 fb−1. A sizeable contribution from the isospin conserving χc1(3872)→ωJ/ψ decay is established for the first time, (21.4±2.3±2.0)%, with a significance of more than 7.1σ. The amplitude of isospin violating decay, χc1(3872)→ρ0J/ψ, relative to isospin conserving decay, χc1(3872)→ωJ/ψ, is properly determined, and it is a factor of 6 larger than expected for a pure charmonium state.